Restless roosts: Light pollution affects behavior, sleep, and physiology in a free‐living songbird. (9th June 2017) - Ouyang, Jenny Q.; de Jong, Maaike; van Grunsven, Roy H. A.; Matson, Kevin D.; Haussmann, Mark F.; Meerlo, Peter; Visser, Marcel E.; Spoelstra, Kamiel
Abstract: The natural nighttime environment is increasingly polluted by artificial light. Several studies have linked artificial light at night to negative impacts on human health. In free‐living animals, light pollution is associated with changes in circadian, reproductive, and social behavior, but whether these animals also suffer from physiologic costs remains unknown. To fill this gap, we made use of a unique network of field sites which are either completely unlit (control), or are artificially illuminated with white, green, or red light. We monitored nighttime activity of adult great tits, Parus major, and related this activity to within‐individual changes in physiologic indices. Because altered nighttime activity as a result of light pollution may affect health and well‐being, we measured oxalic acid concentrations as a biomarker for sleep restriction, acute phase protein concentrations and malaria infection as indices of immune function, and telomere lengths as an overall measure of metabolic costs. Compared to other treatments, individuals roosting in the white light were much more active at night. In these individuals, oxalic acid decreased over the course of the study. We also found that individuals roosting in the white light treatment had a higher probability of malaria infection. Our results indicate that white light at night increases nighttime activity levels and sleep debt and affects disease dynamics in a free‐living songbird. Our study offers the first evidence of detrimental effects of light pollution on the health of free‐ranging wild animals. Abstract : The nighttime environment is increasingly polluted by artificial light at night. We show that white light at night increases activity at night, making birds more restless. This increase in activity translates into increased sleep debt and decreases in immune function.